On the significance of recirculation between intakes and outfalls of desalination and thermal power plants - Law, Adrian Wing-Keung (2013)
In this study, a quantitative analysis is performed to examine the effect of recirculation between intakes and outfalls to the operational performance of coastal desalination as well as thermal power plants. The results show that the effect to desalination plants is substantially more significant than that of thermal power plants, with the increase in salinity of the ambient waters near the intake having a direct impact on the operating cost of the desalting process. Thus, it is important to minimise the magnitude of recirculation for the desalination plant. The potentially higher initial capital cost required (such as placing the outfall further offshore) can be compensated by the corresponding savings in the operation cost in the long run.